2023
DOI: 10.3390/medicina60010024
|View full text |Cite
|
Sign up to set email alerts
|

A Short-Duration Gonadotropin-Releasing Hormone Stimulation Test for the Diagnosis of Central Precocious Puberty

Maria Chiara Pellegrin,
Chiara Marzin,
Lorenzo Monasta
et al.

Abstract: Background and Objectives: The gonadotropin-releasing hormone (GnRH) stimulation test is the gold standard method for diagnosing central precocious puberty (CPP), although it requires multiple blood samplings over 120 min. This study aimed to evaluate if a shorter test may have an equivalent diagnostic accuracy. Materials and Methods: We retrospectively reviewed the GnRH tests of 188 consecutive pediatric patients (169 females) referred for signs of early pubertal development. The diagnostic accuracy of the ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…At our center, we conduct the GnRH test using a fixed administration of 50 mcg of gonadorelin acetate. Although we cannot rule out the possibility of insufficient stimulation, we have observed that in girls with an LH peak greater than 5 IU/L, the mean dosage of gonadorelin per body weight was lower than in others [ 31 ].…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…At our center, we conduct the GnRH test using a fixed administration of 50 mcg of gonadorelin acetate. Although we cannot rule out the possibility of insufficient stimulation, we have observed that in girls with an LH peak greater than 5 IU/L, the mean dosage of gonadorelin per body weight was lower than in others [ 31 ].…”
Section: Discussionmentioning
confidence: 76%
“…Our research supports the findings of Pellegrin et al, who discovered that a 30 min GnRH test has a high sensitivity rate of 99.03% and specificity in diagnosing CPP in females. Additionally, two samples collected after 30 and 60 min, respectively, provide 100% sensitivity and specificity in diagnosing CPP in both males and females [ 2 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The search for parameters useful in differentiating patients with CPP from those with normal variants of pubertal development is important as clues for diagnosis of early activation of the hypothalamic-pituitary-gonadal axis are not yet standardized to date [ 1 , 35 ], and any potential differences could be helpful to exactly identify cases needing medical assessments with a GnRH test. Our statistical analysis showed no significant differences in the lipid profile between children having CPP and not: in fact, despite HDL cholesterol was lower in the CPP group, this association was not confirmed at the multivariate analysis after adjustment for confounding factors.…”
Section: Discussionmentioning
confidence: 99%